Authenticating culture in imperial Japan : Kuki Shūzō and the rise of national aesthetics - Pincus, Leslie, 1950- (Twentieth-century Japan, 1996)
Nearly a half century after Japan opened its doors to Western knowledge, intellectual discourse there took a sharp turn inward. Drawing on the cultural resources of a forgotten past, Japanese thinkers of the 1910s and 1930s imagined a realm of authenticity impervious to the fragmenting processes of modernization. Ultimately these thinkers equated authenticity with something irreducibly Japanese and in so doing became complicit, even instrumental, in a repressive and imperialist state apparatus. How did this cultural complicity take shape, and what does it reveal more generally about the troubled relationship between modernity and national culture?